DISCOURSES ON DEMOCRACY WITHIN DEBATES ON STATE-ISLAM RELATIONS IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2008)
This study discusses the discourse on democracy within the context of the larger debate on Islam-state relations in Indonesia and correlates the religious approach with theories of democracy. It begins with a brief description of types of democracy formulated by political scientists in order to help us classify the Islamic groups efforts in the process of democratization in Indonesia. This is followed by an exploration of these groups views of democracy and their classification on the basis of their religious approach. The study considers both the debate about Islam-state relations and democracy as a competitive process over the interpretation of the predominant Islamic doctrine among the silent majority of the people. This study will also explore the role which Islam should play in the process of democratization. I will argue that the compatibility of Islam with democracy and democratization in the modern sense depends on the identification of universal values.